Performance, Carcass Characteristics and Economy of Production of Broilers Fed Maize-Grit and Brewers Dried Grain Replacing Maize - Anyanwu, G.A.; Iheukwumere, F.C.; Emerole, C.O. (International Journal of Poultry Science, 2008)
A 28-day feeding trial involving ninety-six (96) four weeks old broiler chicks was conducted to investigate the effect of total replacement of maize with different combination ratios of maize grit and Brewers Dried Grain (BDG) on the performance, carcass characteristics and economy of finisher broilers. Four experimental diets were formulated by substituting maize with maize grit and BDG in the ratio of T1 (0%); T2 (3:1-45 + 15); T3 (1:1-30 + 30) and T4 (1:3-15 + 45) respectively. The birds were randomly assigned to four treatment diets. Each experimental unit of 24 birds was replicated twice giving 12 birds per replicate in a completely randomized design (CRD). Feed and water were provided ad-libitum. Body weight and weight gain per feed intake through higher at high cost with the control diet improved in cheaper diets formulated with maize grit and BDG. There was no consistency in the carcass characteristics of the groups particularly among the internal organs showing that dietary maize grit ad BDG could not pose any discernible nutritional problems that might manifest in the carcass of the broilers. Cheaper feed formulated with maize grit and BDG gave the higher gross margins especially diet 4.